(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This article explores the regulatory frameworks governing intangible assets across three key standards: IAS 38 (accounting), IVS 210 (valuation), and ISA 620 (auditing). Employing both automated and manual similarity analysis techniques, the study investigates the structural and thematic alignment of these standards. Principal Component Analysis (PCA) using Voyant Tools and Python-based machine learning techniques, specifically TF-IDF vectorization and cosine similarity analysis, provide an initial textual similarity assessment, followed by a binary-variable-based statistical analysis using SPSS. The study categorizes the comparative analysis into four major themes: recognition and measurement, disclosure and reporting, valuation approaches, and audit considerations. Findings indicate strong alignment between IAS 38 and IVS 210 regarding recognition criteria, valuation methods, and disclosure practices, while ISA 620 exhibits divergence due to its broader audit-centric focus. The results highlight potential gaps in standard harmonization and suggest avenues for refining the treatment of intangible assets in financial reporting, valuation, and auditing frameworks.